(untitled) (World Bulletin of Public Health, 2026)
The physiological senescence of the renal and hepatic systems in advanced age fundamentally alters the systemic disposition of antiviral agents, precipitating a narrow therapeutic index that borders on toxicity. This study evaluates the precise pharmacokinetic parameters and clinical outcomes of utilizing predominantly renally excreted antivirals in a vulnerable geriatric demographic. A prospective observational cohort study was conducted involving 134 elderly patients (ages 65–89) diagnosed with viral infections necessitating systemic therapy, predominantly Herpes zoster reactivation and severe Influenza A. Subjects were stratified based on their baseline renal hemodynamics and the dosing strategy applied: an unadjusted empirical dosing group (n=62) and a dynamically adjusted, targeted dosing group (n=72). Clinical data indicate a profound risk of iatrogenic complications when standard adult reference ranges are applied to this demographic. The unadjusted cohort demonstrated a 28.4% incidence of transient acute kidney injury and subclinical neurotoxicity, directly correlating with the accumulation of hydrophilic drug metabolites. The targeted group, utilizing precise dose reductions corresponding to calculated glomerular filtration rates, exhibited an 82.5% reduction in these adverse events while maintaining identical viral eradication timelines. The dynamics of the observed results suggest that the chronological age of the patient is a critical, independent variable in antiviral pharmacotherapy. Comprehensive therapeutic protocols must integrate individual host variables, specifically the age-related decline in tubular secretion and glomerular filtration, to optimize viral suppression and prevent severe dose-dependent toxicity in the elderly.